Characterization of Flow Separation around Inline Cylinders within Oscillatory Flow - Yiding Zhao; Yao Shi (Shock and Vibration)
This paper has examined the effects of Reynolds number (Re), Keulegan–Carpenter number (KC), and gap ratio on flow separation around a cylinder array by PIV method in experiment. The vortex shedding in such situation occurs each half period of the oscillatory motion from the observation. No matter how many cylinders, KC is the key dominant parameter under low Re that has a great impact on the flow regime and flow motion in oscillatory flows. There is an influence area of vortex shedding around the cylinder. When two inline cylinders are in the flow, smaller gap ratio may extend the influence area of the vortex shedding. For s/d = 2, the vortex shedding that happens in each cylinder has a simultaneity and independence. For s/d = 1.5, the reduced gap ratio leads the upstream shed vortex to interact with downstream cylinder and makes the influence area of vortex shedding around downstream cylinder extends further. For s/d = 1, the interference in the central area is significantly obvious and the vortex shedding is suppressed and even follows the cross gap flow.